Cloacoplasty in a 40-Day-Old Monk Parakeet with Cloacal Prolapse - Cassanego, Guilherme Rech; Ferreira, Priscila Inês; da Rosa, Carolina Cauduro; Flores, Fabiano da Silva; Corrêa, Luís Felipe Dutra (Acta Scientiae Veterinariae, 2021)
Background: The monk parakeet (Myiopsitta monachus) is also known as the quaker parrot and belongs to the order Psittaciformes in the family Psittacidae. The cloaca is a posterior orifice common to reproductive, digestive and urinary systems and the cloacal prolapse is the displacement or inversion of its anatomic position. Nowadays, the non-conventional pet market in Brazil is rapidly growing, which demands more skills and competences from an avian veterinarian. This study case has as its main objective to present a 40-day-old monk parakeet (Myiopsitta monachus) with cloacal prolapse, treated using the cloacoplasty technique. It is important to mention that the occurrence of cloacal prolapse in this species and in such an early age is uncommon. Case: The patient presented 1 day before the physical examination an increased volume in the cloacal region and hematochezia, and diagnosed as cloacal prolapse. For the treatment, wounds were washed using physiological saline solution, ice and sugar were applied in order to reduce the edema, and mineral oil was used for repositioning the cloacal mucosa. Finally, local anesthesia was applied and 2 isolated contralateral sutures were done with the objective of reducing the sphincter’s diameter, without compromising the flow of urine and feces. The monk parakeet was treated with antibiotic Avitrin®) [oxytetracycline hydrochloride - 8.1 mg/mL] and a vermifuge [mebendazole 50 mg/mL]. A sample of feces was also obtained and sent to the Laboratory of Avian Pathology Diagnosis. The patient was discharged after 7 days of the treatment, obtaining a favorable result with no further complications. Discussion: The results of the coproparasitological examination were negative for the samples analyzed; nevertheless, the possibility of a false negative result cannot be totally dismissed. Cloacal prolapse may be related to cases of hypersexual disorder or overexertion to defecate due to intestinal parasites, posture, polyps, enteritis, neoplasm or cloacal hyperplasia. Besides that, endoparasitism is common in captive birds. For the correct treatment, proceed with a cloacoplasty, in which 1 or 2 simple sutures are made separated laterally in both sides, promoting the narrowing of the orifice. The surgeries such as the cloacoplasty are currently being defended, but in most cases as an adjuvant therapy. Cloacal prolapse in birds is a disease considered as an intestinal emergency. The techniques presented in this work demand sedation or anesthesia for the patient, which were not authorized by the tutor due to the high risk involved. However, due to the characteristic of domestication and docile behavior of the bird, it was possible to perform the 2 sutures with a local anesthetic block only. Cloacal prolapse is relatively common in adult psittacine birds, but uncommon in monk parakeets and young birds. The treatment performed was effective for the monk-parakeet presented in this study case. The authors, however, would like to strongly reinforce the need to identify the cause of cloacal prolapse in order to properly treat it. The importance of correctly identifying the anatomy of a psittacine bird as well as applying precisely the suture techniques are the most important conclusions obtained, making both the identification of the problem and its solution through surgical intervention a simpler and successful process. Keywords: birds, endoparasites, suture, wild.